2012
DOI: 10.1007/s00425-012-1693-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in the plant response to abiotic stress

Abstract: As sessile organisms, plants have to cope with the ever-changing environment as well as with numerous forms of stress. To react to these external cues, plants have evolved a suite of response mechanisms operating at many different levels, ranging from physiological to molecular processes that provide the organism with a wide phenotypic plasticity, allowing for fine tuning of the reactions to these adverse circumstances. During the past decade, non-coding RNAs (ncRNAs) have emerged as key regulatory molecules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 142 publications
0
23
0
Order By: Relevance
“…However, during salinity stress, miR169 was significantly induced which halted the expression of nfya5 in Arabidopsis (Kong et al, 2014). In addition, ABA treatment to the Arabidopsis had significantly induced NFYA5 TF and caused the downregulated of miR169 level (Contreras-Cubas et al, 2012; Cheng et al, 2016). …”
Section: Mirna and Ny-fa: Contribute Drought Resistancementioning
confidence: 99%
“…However, during salinity stress, miR169 was significantly induced which halted the expression of nfya5 in Arabidopsis (Kong et al, 2014). In addition, ABA treatment to the Arabidopsis had significantly induced NFYA5 TF and caused the downregulated of miR169 level (Contreras-Cubas et al, 2012; Cheng et al, 2016). …”
Section: Mirna and Ny-fa: Contribute Drought Resistancementioning
confidence: 99%
“…For cetain miRNA families, it has not been reported that these miRNAs were responsive to abiotic stresses in rice, but they were validated to be stress-responsive in other plant species according to previous studies. For instances, miR171 of Arabidopsis is induced by drought stress (Contreras-Cubas et al, ;Liu et al, 2008). In our study, we found that many miR171 family members (osa-miR171b, osa-miR171c-3p, osa-miR171d-3p, osa-miR171e-5p, osa-miR171e-3p, osa-miR171f-5p and osa-miR171f-3p) were also drought-responsive in rice, but they were repressed by water deficit.…”
Section: Panicle_drought_up_srna7099 and Panicle_drought_up_srna7393)mentioning
confidence: 72%
“…In our study, we found that many miR171 family members (osa-miR171b, osa-miR171c-3p, osa-miR171d-3p, osa-miR171e-5p, osa-miR171e-3p, osa-miR171f-5p and osa-miR171f-3p) were also drought-responsive in rice, but they were repressed by water deficit. In common bean (Phaseolus vulgaris), miR2118 is up-regulated under water deficit (Contreras-Cubas et al, ;Arenas-Huertero et al, 2009). Notably, we discovered that osa-miR2118f, osa-miR2118h, osa-miR2118j, osa-miR2118k and osa-miR2118m were also inducible by drought stress in rice panicles.…”
Section: Panicle_drought_up_srna7099 and Panicle_drought_up_srna7393)mentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast to small ncRNAs, only a few lncRNAs have been identifi ed and functionally characterized further to implicate their involvement in abiotic stress response in plants (Ben Amor et al 2009 ;Contreras-Cubas et al 2012 ).…”
Section: Role Of Lncrnas In Abiotic Stress Tolerancementioning
confidence: 98%